Racismo e inmigración en Cuba en el siglo XIX / Consuelo Naranjo Orovio, Armando García González ; prólogo de Josef Opatrný - García González, ArmandoOpatrný, Josef; Naranjo Orovio, Consuelo (Colección Antilia)
Bibliogr.: p. [215]-233